Language Portraits: Investigating Embodied Multilingual and Multimodal Repertoires - Kusters, Annelies; De Meulder, Maartje (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2019)
In this article, we discuss the use of language portraits (LP) as a research method to investigate the embodied multilingual repertoires of people who use both spoken and signed languages. Our discussion is based on two studies in which most participants were deaf (one study also included hearing participants). We primarily offer a methodological contribution to the discussion around LP, since we argue that the study of linguistic repertoires of signers takes the multimodal aspect of the method to a new level. Indeed, by separating modalities (speech, signing, writing), grouping languages in different ways, and mapping them on the LP, the LP discussed in this article represent multimodal languaging more explicitly than in previous studies. Furthermore, by locating particular signs on the LP, several participants literally mapped their body when signing and gesturing in their narratives, thus performing and becoming their language portrait. We suggest that the study of body language (signing/gesturing/pointing) in the verbal narrations accompanying the LP thus expands the multimodal aspect of the analysis of LP.